Impacto térmico das mudanças climáticas sobre o desenvolvimento fenológico das principais culturas agrícolas do Brasil - Robles, Tiago Capello (2018)
Positive climate change trends and the increasing potential of climate impacts made crucial to adapt agricultural crops due to these changes and adjust the use of natural resources in a more sustainable way. The aim of the present work is to make a global warming impact preliminary analysis on phenological development of the foremost crops in Brazil. Thus, two representative concentration pathways (RCP2.6 and RCP8), climate change scenarios, were used, generated from Hadley Center Global Environment Model version 2 Earth System (HadGEM2-ES) and regionalized with Regional Climate Model version 4 (RegCM4) for forthcoming air temperature data series (2070-2099) that were paired with a reference series (1976-2005). In order to assess global warming impact on cotton, irrigated rice, corn, soybean and wheat crop development cycles, the concept of daily Thermal Sum (dTS, ° C day) was used, which establishes the fact that the rate of daily development of a plant is linked to air temperature, assuming the existence of cardinal temperatures Tb, Top and Tmax. Main results revealed that heating conditions of the RCP2.6 scenario approached the average air temperature (Ta) of the maximum development values (Top), contributing to a faster development and, therefore, a decrease in cycle duration. In Paraná state under RCP8.5 scenario heating conditions, adverse impacts are observed for corn, soybean, irrigated rice and wheat crops development. Same scenarios were observed in Center-West producing regions, were, in addition to lengthier phenological phases, crops will suffer thermal stress because the Ta approaches the maximum Tmax limits, which will lead to a reduction of the cultivable area. For the case of irrigated rice and wheat from Paraná, the negative effects are kinder, but might cause a small area reduction.